Evaluating spatial disparities of rotor sites and high dominant frequency regions during catheter ablation for PersAF patients targeting high dominant frequency sites using non-contacting mapping - Ehnesh, Mahmoud; Li, Xin; Almeida, Tiago P.; Chu, Gavin S.; Dastagir, Nawshin; Stafford, Peter J.; Ng, G. André; Schlindwein, Fernando S. (Frontiers in Physiology, 2022)
Purpose: Several studies have emphasised the significance of high dominant frequency (HDF) and rotors in the perpetuation of AF. However, the co-localisation relationship between both attributes is not completely understood yet. In this study, we aim to evaluate the spatial distributions of HDF regions and rotor sites within the left atrium (LA) pre and post HDF-guided ablation in PersAF. Methods: This study involved 10 PersAF patients undergoing catheter ablation targeting HDF regions in the LA. 2048-channels of atrial electrograms (AEG) were collected pre- and post-ablation using a non-contact array (EnSite, Abbott). The dominant frequency (DF, 4-10 Hz) areas with DF within 0.25 Hz of the maximum out of the 2048 points were defined as ‘high’ DF (HDF). Rotors were defined as PSs that last more than 100 ms and at a similar location through subsequent phase frames over time. Results: The results indicated an extremely poor spatial correlation between the HDF regions and sites of the rotors in pre- versus post-ablation cases for the non-terminated (pre: CORR; 0.05 ± 0.17. Vs. post: CORR; – 0.030 ± 0.19, and with terminated patients (pre: CORR; – 0.016 ± 0.03. Post: CORR; – 0.022 ± 0.04). Rotors associated with AF terminations had a long-lasting life-span post-ablation (non-terminated Vs. terminated 120.7 ± 6.5 ms Vs. 139.9 ± 39.8 ms), high core velocity (1.35 ± 1.3 mm/ms Vs. 1.32 ± 0.9 mm/ms), and were less meandering (3.4 ± 3.04 mm Vs. 1.5 ± 1.2 mm). Although the results suggest a poor spatial overlapping between rotors’ sites and sites of AFCL changes in terminated and non-terminated patients, a higher correlation was determined in terminated patients (spatial overlapping percentage pre: 25 ± 4.2 % Vs. 17 ± 3.8 % Vs. post: 8 ± 4.2 % Vs. 3.7 ± 1.7 % P < 0.05, respectively). Conclusions: Using non-contact AEG, it was noted that the correlation is poor between the spatial distribution of HDF regions and sites of rotors. Rotors were longer-lasting, faster and more stationary in patients with AF termination post-ablation. Rotors sites demonstrated poor spatial overlapping with sites of AFCL changes that lead to AF termination.